Mulheres no turismo de base comunitária em áreas protegidas: uma análise sobre suas atuações na Amazônia Paraense - VIANA, Janise Maria Monteiro Rodrigues (Universidade Federal do Pará, 2024)
Tourism activity, in its multiple modalities, is a global phenomenon that encompasses complex perspectives of the indissociability between cultures and biodiversity. In this context, women have been emerging as drivers of tourist praxis. This work, therefore, addresses the theme of women and tourism in protected areas in the Pará Amazon. The research loci were the communities of Vila de Anã, São Miguel/São Marco, Tucumã, Maripá and Resex Vista Alegre do Capixauã, located in the Tapajós-Arapiuns, and the communities of Jamaraquá, Maguari and São Domingos, in the Tapajós National Forest, in the municipalities of Santarém and Belterra. The general objective of this study is to analyze the role of Amazonian women in the development of Community-Based Tourism, their modes of organization and action in the activity and for the environmental sustainability of the territories where they live. To this end, it sought to know who are the women involved in tourism; what is their understanding of TBC and to what extent it is composed of an effective tool for gender equality and empowerment; identify the implications that TBC can generate for women involved in the activity; and understand how they act to achieve the objectives of Protected Areas and environmental sustainability. The research was based on a qualitative and quantitative analysis with an interdisciplinary approach, based on a bibliographic survey focusing on women, tourism, protected areas, and the Amazon. Documentary research was also carried out, as well as data collection and observation through field research, the use of semistructured interviews with agents involved in the relationship between tourism and protected areas, and the use of audio and photographic recording. The results obtained indicate that the practice of TBC is established as a constant in the communities studied in the TapajósArapiuns Resex and the Tapajós Flona, as well as that female action constitutes the driving force for its development and to think about the relationship of social actors with the management of natural resources and sustainability. The insertion of women in Tourism, especially of Amazonian women, are strategic and essential to break with prejudice and the devaluation of female work and to recognize that they are protagonists to make the activity feasible in contexts of protected areas. The focus on women can support reflections and research on tourist activity in its varied practices, as well as to think about sustainability in dealing with natural and social resources, and also in the sociocultural reproduction of the Amazonian population.